Urban decay and regeneration strategies in small towns : a case study of Thohoyandou , South Africa - Magubane, Philani Brandon (My University, 2024)
Evidence of urban decay in small South African towns has been increasingly discernible over the years. Undoubtedly, other small rural towns face a myriad of challenges attributable to historic apartheid planning. They are distressed and underperforming despite having urban regeneration strategies in place. Small towns are faced with high poverty, unemployment, and a lack of economic vitality and diversification, creating a high degree of stagnation and urban decay. This complexity has been exacerbated by the vulnerability to Covid-19 pandemic stress, adding new challenges affecting their liveability and vitality. This resulted in renewed interest in small towns’ regeneration by the South African government to foster the developmental role of small towns. This dissertation contributes to the debate on how to improve current regeneration strategies in small towns focusing on Thohoyandou Town Central Business District (CBD). This study's objectives were threefold: firstly, to characterise urban decay through mapping, secondly, to investigate the causes and thirdly, to recommend a framework for sustainable small town urban regeneration. This study adopted a case study research design, augmented by the mixed method research approach. The SW Maps mobile application was used to gather geospatial data on urban decay in Thohoyandou Town CBD. This was complemented by questionnaire data collected from 202 participants and 3 key informants’ interviews. The spatial data were analysed through ArcMap geospatial analysis tools to produce maps reflecting the spatial extent and intensity of urban decay in Thohoyandou Town CBD. The data attained from study participants were analysed through ATLAS. ti, Microsoft Excel, and Statistical Package for the Social Sciences (SPSS) using thematic analysis and descriptive statistics. The study findings are that empirically Thohoyandou Town CBD is grappling with urban decay. This is caused by several key blockages, including poor urban management and planning, poor service delivery, the Covid-19 pandemic, implementation challenges caused by political interference, lack of monitoring and evaluation system, lack of policy alignment, and poor governance and inadequate institutional capacity linked to staff shortages with appropriate expertise. The implications of these findings are that current strategies are limited and outdated. The current urban regeneration strategy needs to be revised to enhance policy alignment, considering other funding modalities and establishment of special public entities to implement the strategies. More importantly, successful regeneration of small towns requires resources, patience, and commitment. Therefore, a stronger political will, effective governance, public-private cooperation, and institutional capacity are required to enable small rural towns to remain viable and transform into viable, vibrant and liveable cities.
M.URP
Department of Urban and Regional Planning
Keywords: Thulamela Local Municipality; UCTD; Urban decay; Urban regeneration; Small town